Effect of rta on electrical characteristics of pt-doped p-n junction diode - Chaiyasoonthorn, Sawatsakorn; Srithanachai, Itsara; Sangwaranatee, Narong (My University, 2017)
This paper investigates the effect of rapid thermal annealing (RTA) between 850 and 900°C. Platinum (Pt) atom will drive-into silicon structure by using RTA process and the influence of temperature. Therefore, we study the effects of temperature in RTA process to I-V characteristics of device are 850 and 900°C at 15 mins. After annealing process, the built-in voltage (Vbi ) is around 0.3-0.4eV, which means that Pt does not affect the device junction. The I-V characteristics after annealing show that at 900°C there is the worst leakage of current with slightly better than the forward current. In case of leakage current, it may occur from the Pt atom damage creation or trapping center in silicon structure.
Keywords: I-V characteristics; Platinum (Pt); Rapid thermal annealing (RTA)